Methodological Characteristics of Teaching English in Preschool and Primary Schools - Maxkambayeva Ozoda Xusan Qizi (Zien Journals, 2022)
The article describes the essence of the organization of non-traditional lessons on the basis of a new approach to the preschool education system, the role and importance of the use of new technologies in teaching English to kindergarten children. The use of didactic games in the classroom, based on its effect on the effective mastery of topics by children, methodological features of teaching English in preschool and primary education, further increase children's interest in English, their impact on psychology, the teaching of creative thinking from an early age, as well as the methodological features of teaching and learning based on the methodology of continuous education to date.
Keywords: Didactic games; non-tradition; interactive games; logic thinking